How do you simplify (x^2-9)/(x+2)div(x^2+x-6)/(x^2-4)?

1 Answer
May 2, 2018

Invert the divisor polynomial, then multiply (factor) and simplify.
(a/b)/(c/d) = (a/b) * (d/c) = (a*d) / (b*c)

Explanation:

(x^2-9)/(x+2)div(x^2+x-6)/(x^2-4)= ,invert the divisor and multiply

(x^2-9)/(x+2)*(x^2-4)/(x^2+x-6)=

((x^2-9) * (x^2-4)) / ((x+2)*(x^2+x-6))= ,then factor and reduce

((x+3)(x-3)(x+2)(x-2)) / ((x+2)(x+3)(x-2))=

((cancel(x+3)) (x-3) (cancel(x+2)) (cancel(x-2))) / (cancel((x+2))cancel((x+3)) cancel((x-2)))=

x-3